Relationship between quality of life and unprotected anal intercourse among Chinese men who have sex with men: a cross-sectional study - Yaxin Zhu; Jie Liu; Bo Qu; Bingxue Hu; Yang Zhang (BMC, 2016)
Abstract Background The prevalence of unprotected anal intercourse (UAI) is high among Chinese men who have sex with men (MSM). As important aspects of quality of life (QOL), psychological health and social relationships have been found to be associated with UAI among MSM, which was of great concern for intervening on UAI. Methods We conducted a cross-sectional study in Zhengzhou, Henan province, and in Huludao, Liaoning province, China, to measure quality of life (QOL) using the brief version of the World Health Organization Quality of Life (WHOQOL-BREF). Cronbach's α coefficient was used to test the internal consistency of the questionnaire items, and construction validity was assessed by exploratory factor analysis. T-test, chi-square test and multivariate logistic analysis were carried out to test the relationship between quality of life and unprotected anal intercourse. Results The questionnaires of 320 of the 373 men who have sex with men that were surveyed met our validity criteria (response rate: 85.8 %). A total of 161 subjects (50.3 %) reported having unprotected anal sex in the last 6 months. The results of univariate analysis indicated that having unprotected anal sex was significantly associated with psychological health (PSYCH), social relationships (SOCIL), age, and marital status (P-value <0.05). The 3 items ("Negative feelings", "Hopeness on your life", and "Be able to concentrate") in the PSYCH subscale were associated with UAI significantly (P-value <0.05). Multivariate analysis showed that psychological health (adjusted odd ratio (AOR) 0.979, 95 % confidence interval (CI) 0.961-0.998) was independent factor affecting the likelihood of having UAI in the population of Chinese MSM, and participants who aged 45 or more had higher odds of UAI (AOR 3.986, 95 % CI 1.199-13.255). Conclusions WHOQOL-BREF was acceptable for evaluating the quality of life of MSM. Psychological health, as one important aspect of quality of life, was negatively associated with unprotected anal intercourse. The finding underscored the needs to incorporate the strategies on improving psychological health into the UAI intervention to reduce the HIV transmission among MSM.